(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hervani D, Sari SP. 2022. The abundance of arthropods and natural enemies on two growth phases of hybrid corn, Solok District, Indonesia. Biodiversitas 23: 2966-2972. Solok District, West Sumatra, Indonesia is one of Indonesia’s hybrid corn production regions. As yet, the study of arthropods is still limited. This study aimed to study the abundance and diversity of arthropods in the hybrid maize agroecosystem in Solok District, West Sumatra. The research was conducted from May to November 2020 in Tanah Garam Sub-district, Solok District. The sampling was carried out four times in two growth phases of hybrid corn: vegetative (the age of 20 and 40 days after planting/DAP) and the generative phase (the age of 60 and 80 DAP). The arthropod collection was conducted using a yellow trap and a modified vacuum technique. The identification process was carried out at the Insect Bioecology Laboratory, Andalas University. The study found two classes of arthropods in a hybrid cornfield in Solok District, namely Arachnida and Insecta. The Shannon-Weiner diversity index value (H’) was 1.383, and the evenness index of species (J’) was 0.997. A total of 2,927 individual arthropods, 80 families, 8 orders, and 3 classes, were recorded in the hybrid corn ecosystem in Solok District. Insect class (2,866 individuals) dominated the diversity of arthropods, where the majority of the arthropods found belong to groups of natural enemies such as predators and parasitoids. Conservation of natural enemies (predators and parasitoids) is one of the main factors in supporting the success of pests biologically, so the act of identifying natural enemies in an area is very important.